[Afisz. Incipit] Cudna plaża w Jelitkowie ... (Gdańsk : [wydawca nieznany], 1947)
Afisz reklamujący Jelitkowo i bar Morskie Oko.
Keywords: Jelitkowo (Gdańsk, Polska ; dzielnica) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.